Trifocal toric intraocular lenses in eyes with low amount of corneal astigmatism - Paz Orts-Vila; Salvador Aguilar-Córcoles; Cristina Tello-Elordi; María Ramos-Alzamora; Robert Montés-Micó; Pedro Tañá-Rivero (International Journal of Ophthalmology, 2020)
AIM: To evaluate the refractive and visual outcomes following cataract surgery and implantation of a trifocal toric intraocular lens (IOL) in eyes with low degrees of corneal astigmatism. METHODS: Twenty-six eyes of 22 patients who underwent implantation a trifocal toric IOL (FineVision PODFT, PhysIOL s.a., Liege, Belgium) were enrolled. Phacoemulsification with femtosecond laser, capsular tension ring insertion and intraoperative aberrometry were performed in all cases. All IOLs used showed a cylinder power of 1.00 D. Main outcome measures were refractive error and corrected-distance visual acuity (CDVA) and uncorrected-distance visual acuity (UDVA) values. Eyes were evaluated at 4mo post-surgery. RESULTS: Totally 50% of eyes showed a spherical equivalent (SE) within ±0.13 D and all of them within ±0.50 D. The mean SE and refractive cylinder were -0.02±0.23 and -0.16±0.22 D, respectively. Vector analysis revealed that 100% of eyes were within ±0.50 D for the SE and cylindrical components (J0 and J45). Refractive changes were not correlated with keratometric changes (P>0.05) showing that the reduction in astigmatism comes from the trifocal toric IOL. Of 81% and 96% of eyes showed UDVA and CDVA of 20/20, respectively. The postoperative mean values of monocular distance Snellen decimal UDVA and CDVA were 0.97±0.05 and 0.99±0.02 (about 20/20), respectively. CONCLUSION: Our study suggests that the use of this trifocal toric IOL in patients with low amount of astigmatism provides accurate refractive outcomes and enables them to achieve excellent visual acuity.